2013
DOI: 10.1111/1754-9485.12012
|View full text |Cite
|
Sign up to set email alerts
|

Novel 3D conformal technique for treatment of choroidal melanoma with external beam photon radiotherapy

Abstract: In this small series, a novel non-stereotactic technique was found to be an accurate method for the treatment of CM with a high rate of freedom from tumour progression, in keeping with the SRT series. The quality of the conformal plan was variable. Investigation of the optimal dose-fractionation schedule to minimise late radiation toxicity without compromise of tumour control is the focus of ongoing clinical research at our centre.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The COMS results showed that patients with medium-sized CM did not have significantly different mortality rates at 12 years, irrespective of whether they were treated with PB or were subjected to enucleation. The apparent equivalence of treatments resulted in the exploration of episcleral PB, proton-beam treatment, and SRT as eye-preserving treatments [ 2 , 7 , 11 , 14 , 15 , 21 - 23 , 29 , 31 , 34 , 35 ]. Following COMS, medium-sized or smaller CMs are treated mainly with brachytherapy [ 14 , 22 ] while tumor control has been associated with a minimum dose to the tumor (Dmin) of 85 Gy delivered to the apex of the tumor as the gold standard [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The COMS results showed that patients with medium-sized CM did not have significantly different mortality rates at 12 years, irrespective of whether they were treated with PB or were subjected to enucleation. The apparent equivalence of treatments resulted in the exploration of episcleral PB, proton-beam treatment, and SRT as eye-preserving treatments [ 2 , 7 , 11 , 14 , 15 , 21 - 23 , 29 , 31 , 34 , 35 ]. Following COMS, medium-sized or smaller CMs are treated mainly with brachytherapy [ 14 , 22 ] while tumor control has been associated with a minimum dose to the tumor (Dmin) of 85 Gy delivered to the apex of the tumor as the gold standard [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Variations of these 3 treatment modalities are SRT and CPRT (which, in the case of OM, mainly refers to PBT), linear accelerator (LINAC)-based SFRT, and GK radiosurgery [ 13 - 15 , 17 ]. Today, RT has become the treatment of choice for medium-sized and symptomatic small CMs [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the irradiation sessions, the head and eye must be carefully positioned. Although the efficacy seems to be similar to brachytherapy (59), there are major advantages due to more homogenous and focused treatment and less damage on the surrounding tissue (60). Still, radiation-associated complications can occur in time in almost 50% of the cases (61).…”
Section: Irradiation Therapiesmentioning
confidence: 99%
“…This type of approach requires the patient to gaze at the light source during each fraction of radiation delivery. Other tracking systems have also been proposed [1,2,27,34], which are mostly focused on the reproducible stereotactic frame and automatic real-time surveillance of the eye position. These approaches share a common feature that the monitoring system serves as a gating role for radiation delivery, i.e., if the captured eyeball information deviates out of a predefined range, an interruption signal will be sent to LINAC and the radiation beam will be paused.…”
Section: Introductionmentioning
confidence: 99%